ÇARLIK DÖNEMİNDE KIRGIZLAR (1852-1917) - YAZI, MUHAMMET EMİN (Fırat Üniveristesi, 2007)
Kırgızistan ülkesinin en eski halkı burada M.Ö. 5-6. yüzyıldan beri ikametetmekteydi. İlk Kırgızlar Tien Şan Dağları çevresinde boylar halinde göçebe bir yaşamsürüyorlardı. Daha sonra ortaçağda vuku bulan birçok savaş ve diğer hadiselerden sonraKırgız halkının başka coğrafyalara dağıldığını görüyoruz. Onuncu yüzyılda otlak aramak içinve başka toplumların da baskısıyla-özellikle Moğollar-bugünkü Kırgızistan topraklarınagelene kadar güneye göç etmeye başlamışlardır. 18. yüzyıl başlarında bölgenin en kalabalıknüfusunu oluşturuyorlardı.Rusya'nın Kırgızistan'I işgali 19. yüzyılın ortalarında başladı. Kırgızistan, Rusya'nınana sömürgesi haline geldi. Topraklar Rus göçmenlere verilmeye başlandı. Rus sömürüsiyaseti ve dayattığı mecburi askeri yükümlülükler, Orta Asya'da Kırgızların da içindebulunduğu büyük bir isyan hareketi başlattı. Bundan her iki taraf da büyük zarar gördü.Birçok Kırgız, Afganistan ve Çin'e göç etti.Çarlık hükümeti Kırgızları ayrı bir ulus olarak tanımadı. Kırgızistan Orta Asya'dakidiğer Türk ulusları gibi 1867'de kurulan Türkistan Genel Valiliği içine dahil edildi. Kırgızlar1916 yılında Ruslara karşı isyan ettiler ve bu isyan kanlı bir şekilde bastırıldı.Anahtar Kelimeler: Kırgızistan, Çarlık Rusya

The earliest settlers in the land, that is now Kyrgyzstan, arrived as early as the 5th or6th centuries BC. The early Kyrgyz lived a nomadic life in tribal groups, living in relativeseclusion around the mountain of the Tien Shan. Their isolation separated them from many ofthe wars and other events that took place in Central Asia during the early Middle Ages. In thetenth century they apparently began migrating south searching for new pastures or driven byother people--particularly the Mongols in the thirteenth century--until they settled in thepresent-day Kirgiz Republic. By the early sixteenth century, they were the area's predominantpeople.Russian conquest of the Kirgiz began in the mid-nineteenth century, and by 1876 theywere absorbed into the Russian Empire. Kirgizia became a major area of Russiancolonization, with Russians and other Slavs given the best land to settle, reducingconsiderably the grazing lands used by the Kirgiz nomads. Kirgiz resentment against Russiancolonization policies and conscription for noncombatant duties in the army led to a majorrevolt throughout Russia's Central Asian territory, including Kirgizia. Casualties were high onboth sides, and thousands of Kirgiz fled with their flocks to Afghanistan and China.The tsarist government did not recognize the Kirgiz as a separate national entity orpolitical unit. Kirgizia, along with other Turkic nations of Central Asia, was included inRussian Turkestan, created in 1867. The Kirgiz revolted against the Russians in 1916, theiractions brought swift and brutal suppression.Key Words: Kirgizistan, Tzarist Russia
The Kyrgyz in the Tzarist epoch
Keywords: Tarih